The tourism seasonality in Romania - Diana Necula; Manea Draghici; Raluca Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
One of the problems which establishments managers must deal with is the seasonality from tourism. The seasonality causes may be natural (the seasons succession, climatic conditions), the variety and the cultural values attractiveness, the frequency of events (fairs, festivals, etc.) and economic and organisational (structure of the school year and university year, holidays, increasing the length of leisure time and its redistribution, habits, etc.). In this paper we pursued the seasonality calculation at the country level by calculating the coefficient of the seasonality of accommodation and overnight stays, resulting, for the period 2010-2013, for a total tourist structures an obvious seasonality. The magnitude of seasonal variation and their frequency of manifestation has consequences on the development of tourism and its efficiency, as well as other sectors of the economy, branches that tourism develops in interdependence.
Keywords: 330; tourism seasonality; accommodation capacity; overnight stays